Antihypertensive treatment improves glycemic control in patients with newly diagnosed type 2 diabetes mellitus: A prospective cohort study - Li, Jung-Chi; Cheng, Po-Chung; Huang, Chien-Nin; Jian, Li-Fen; Wu, Ying-Syuan; Lin, Chih-Li (Frontiers in Endocrinology, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder involving progressive pancreatic dysfunction. A substantial proportion of patients with T2DM cannot achieve euglycemia despite pharmacologic therapy. Preceding clinical studies have shown that hypertension contributes to glucose dysregulation, and investigators in this study hypothesized that antihypertensive treatment may improve glycemic control in patients with T2DM. Methods: This prospective cohort study investigates the effect of adding the antihypertensive drug Amlodipine to standard diabetes therapy on serum glycosylated hemoglobin A1c (HbA1c) and lipid profile in patients with newly diagnosed T2DM. The study enrolled a total of 168 participants with newly diagnosed T2DM. Results: Recipients of additional antihypertensive drug Amlodipine demonstrated significantly lower serum HbA1c (6.62% vs. 7.01%, P = 0.01), systolic blood pressure (132 mm Hg vs. 143 mm Hg, P < 0.001), and diastolic blood pressure (78.9 mm Hg vs. 86.0 mm Hg, P <0.001) compared to recipients of standard diabetes therapy after 24 weeks. Conclusion: Antihypertensive treatment with Amlodipine in addition to standard diabetes therapy improves glycemic control in patients with T2DM and may be an appropriate option in people with diabetes and concomitant hypertension to help maintain euglycemia.